Boron Deficiency of Coconut (Cocos nucifera Lin.): A Field Note - Severino S. Magat; Luis G. Cruz (International Coconut Community Journal, 2001)
The soil and external supply of micronutrient boron (B) clearly affect the coconut crop’s growth and development; and, thus, the yield and quality of produce, particularly during the dry season (< 75 mm rainfall/month). A clear deficiency of B in young palms of several farms ( 11 out of 37) was observed in a project site of a nationwide multi-location piloting (MULTILOC ACTPRO) of coconut varieties and hybrids located in an inland area of Linabu, Balingasag, Misamis Oriental, Northern Mindanao, Philippines. The deficiency in young coconut is characterized by the presence of deformed leaf fronds or “little leaf”, followed by non-splitting or delayed opening of leaflets that usually appear in zigzag-like pattern in advanced or severe deficiency stage. The apical shoot blackens, exhibiting growth failure and death of tissues and plant per se. Photographs of the boron deficiencies in sample farms, and recommended correcting measures are presented.